2020
DOI: 10.3389/fnins.2020.00538
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Organoids From Human Pluripotent Stem Cells

Abstract: The brainstem is a posterior region of the brain, composed of three parts, midbrain, pons, and medulla oblongata. It is critical in controlling heartbeat, blood pressure, and respiration, all of which are life-sustaining functions, and therefore, damages to or disorders of the brainstem can be lethal. Brain organoids derived from human pluripotent stem cells (hPSCs) recapitulate the course of human brain development and are expected to be useful for medical research on central nervous system disorders. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 62 publications
2
33
0
Order By: Relevance
“…Population 11 (salmon; top genes C11orf88, ARMC3, CAPSL, CFAP126, MAP3K19, ANKRD66 ) also expressed cilia-related genes DYNC1I2, DYNLRB2, IFT22, TMEM67, FUZ 29 , 30 . Equivalent cell types speculated to represent the ciliated ependymal cells, which line the ventricular walls have been identified in other organoid models 31 , 32 . Expression of population-enriched markers is shown from in situ hybridisation data from the Allen Brain Atlas (ABA), where the majority of markers appeared restricted to specific cell types (Supplementary Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…Population 11 (salmon; top genes C11orf88, ARMC3, CAPSL, CFAP126, MAP3K19, ANKRD66 ) also expressed cilia-related genes DYNC1I2, DYNLRB2, IFT22, TMEM67, FUZ 29 , 30 . Equivalent cell types speculated to represent the ciliated ependymal cells, which line the ventricular walls have been identified in other organoid models 31 , 32 . Expression of population-enriched markers is shown from in situ hybridisation data from the Allen Brain Atlas (ABA), where the majority of markers appeared restricted to specific cell types (Supplementary Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that BMPs and RA are essential for induction of Phox2b-expressing NCCs ( Kirino et al, 2018 ). Eura et al (2020) produced brainstem organoids that contained NCCs, midbrain and hindbrain progenitors as well as noradrenergic, dopaminergic and cholinergic neurons.…”
Section: Generation Of Noradrenergic Neurons In Vitromentioning
confidence: 99%
“…Despite the complexity of the stress system, brain organoids could be invaluable in the modeling of the stress response and stress-related disorders. Advances in brain organoid technologies include functional hypothalamic-pituitary organoids ( Kasai et al, 2020 ), human brainstem organoids containing noradrenergic neurons ( Eura et al, 2020 ), fused forebrain and thalamocortical assembloids ( Birey et al, 2017 ; Bagley et al, 2017 ; Xiang et al, 2017 , 2019 ), midbrain organoids ( Jo et al, 2016 ; Monzel et al, 2017 ; Kim et al, 2019 ; Kwak et al, 2020 ), oligocortical spheroids with oligodendrocytes ( Madhavan et al, 2018 ), hippocampal organoids ( Sakaguchi et al, 2015 ), assembloids integrated with isogenic microglia ( Song et al, 2019a ), vascularized organoids with BBB properties ( Cakir et al, 2019 ), polarized forebrain organoids ( Cederquist et al, 2019 ), sliced forebrain organoids ( Qian et al, 2020 ) ( Supplementary Table 1 ). Central noradrenergic neurons and peripheral sympathetic neurons have been generated from hESCs ( Mong et al, 2014 ; Kirino et al, 2018 ).…”
Section: Challenges and Opportunities: Using Brain Organoids To Model The Stress System And Stress-related Disorders Toward A Unified Thementioning
confidence: 99%
“…To model this phenomenon with brain organoids, both microglial cells and firing neurons with synapses must be included in a single organoid because microglial cells engulf the synapses of neurons with low neuronal activity (Schafer et al, 2012; Figure 2C). Neuronal firing has already been observed in some brain organoids (Giandomenico et al, 2019;Trujillo et al, 2019;Eura et al, 2020), and synapse formation between neurons has also been observed in longcultivated organoids and fused organoids (Birey et al, 2017;Trujillo et al, 2019;Xiang et al, 2019). Microglial cells are not expected to be present in brain organoids because microglial cells are yolk sac-derived mesodermal cells (Gomez Perdiguero et al, 2015), whereas brain organoids are established by neuroectodermal induction.…”
Section: Potential Modeling Of the Synaptic Pruning With Brain Organoidsmentioning
confidence: 99%
“…In 2013, Lancaster et al reported the first method for inducing human cerebral organoids that recapitulate the structure of the ventricles and the neuronal layers of the human cerebral cortex, even though these organoids harbor other various brain regions ( Lancaster et al, 2013 ). Following this report, many protocols for generating organoids that mimic other brain components, including the midbrain ( Jo et al, 2016 ), brainstem ( Eura et al, 2020 ), choroid plexus ( Pellegrini et al, 2020 ), cerebellum ( Muguruma et al, 2015 ), and spinal cord ( Ogura et al, 2018 ; Duval et al, 2019 ), were established. Furthermore, fine-tuned protocols for producing cerebral cortex-specific organoids were later reported ( Paşca et al, 2015 ; Qian et al, 2016 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%